High-barrier flexible nano-cellulose coating, coating and preparation method of high-barrier flexible nano-cellulose coating

Through the flexible polymer cross-linking strategy, a high-barrier flexible nanocellulose coating was prepared, which solved the problem of insufficient barrier properties of polylactic acid films in water and oxygen, and significantly improved its barrier and mechanical properties.

CN119875435AActive Publication Date: 2025-04-25HUBEI UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510120573.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2025-04-25
Estimated Expiration
2045-01-25

AI Technical Summary

Technical Problem

The insufficient barrier properties of polylactic acid films in water and oxygen limit their performance in large-scale commercial applications of food or drug packaging that require high barrier properties.

Method used

Using a flexible polymer cross-linking strategy, the nanocellulose dispersion is oxidized by an oxidizing agent, thiol groups are introduced, and combined with PEGDA cross-linking agent to form a high-density network structure to prepare a high-barrier flexible nanocellulose coating.

Benefits of technology

It significantly improves the water and oxygen resistance capabilities of polylactic acid films, enhances its mechanical strength, thermal stability, transparency and gloss, and improves the overall performance of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875435A_ABST
    Figure CN119875435A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of functional coatings, and particularly relates to a high-barrier flexible nanocellulose coating capable of being used for a polylactic acid film material, a coating and a preparation method of the high-barrier flexible nanocellulose coating. The dialdehyde nanocellulose is prepared by taking nanocellulose crystals as a raw material and sodium periodate as an oxidizing agent and oxidizing hydroxyl into aldehyde groups. The preparation method comprises the following steps: reacting dialdehyde nano-cellulose with cysteine to prepare sulfydryl modified nano-cellulose; then mixing the CNC-cys with a polyethylene glycol diacrylate cross-linking agent and a photoinitiator to form a water-based paint, and then carrying out blade coating, ultraviolet light irradiation cross-linking and room temperature drying processes to obtain the flexible and transparent nano cellulose coating. By adopting the process to coat the surface of the polylactic acid film, a compact, transparent and flexible nano cellulose coating can be formed on the surface of polylactic acid, and a polylactic acid film material with good degradability, flexibility and high barrier is finally obtained and can be used as a green packaging material in the fields of biological health, food preservation, agriculture and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional coatings, and in particular relates to a high-barrier flexible nano-cellulose coating, a coating and a preparation method thereof. Background Art

[0002] Polylactic acid is an aliphatic polyester made from lactic acid. It has good degradation and recycling properties. In the natural environment, polylactic acid can quickly decompose into water and carbon dioxide, fully integrate into the ecological cycle, and leave no harmful residues. Therefore, polylactic acid has become an ideal choice for solving the problem of plastic pollution. In addition, polylactic acid also has good gloss, transparency and mechanical properties, which make it particularly widely used in the field of green packaging materials. However, there are some significant disadvantages in using polylactic acid as a packaging film. For example, the barrier properties of polylactic acid film to water and oxygen are relatively limited, which is mainly due to the ester structure and low crystallinity of its molecular chain. Low crystallinity means that the molecular chains are not arranged tightly enough, which makes it easy for water and oxygen molecules to penetrate through. Therefore, the performance of polylactic acid in large-scale commercial applications of food or pharmaceutical packaging that requires high barrier properties is limited.

[0003] In order to improve the barrier properties of polylactic acid (PLA), a variety of strategies can be adopted, such as modifying the molecular structure of PLA, adding barrier materials, using coating technology or compounding with other materials. Among them, coating technology is an effective solution, which can not only enhance the barrier properties of PLA, but also maintain the environmental protection and sustainability of the material. In recent years, nanocellulose crystals (CNC) have gradually attracted attention as an excellent material. Nanocellulose crystals are highly crystalline one-dimensional nanorods extracted from natural cellulose, with a diameter usually less than 100 nanometers. It has a high aspect ratio and strength, and has excellent biocompatibility. Nanocellulose crystals can form a dense barrier layer, significantly blocking the permeation of water and oxygen, thereby significantly improving the barrier properties of PLA film. In addition, nanocellulose crystals also have excellent optical and mechanical properties, which is particularly important for improving the comprehensive properties of materials. When nanocellulose crystals are used for coating of PLA film, the water and oxygen barrier capabilities of the film can be significantly enhanced. Nanocellulose crystal coating can improve the mechanical strength, thermal stability, transparency and gloss of the film, making the coated PLA film have broad application potential in packaging, food preservation and biomedicine. Especially in the field of food packaging, improved films can better maintain the freshness of food, thereby extending its shelf life.

[0004] Although nanocellulose crystals have many advantages, they still face some challenges. For example, the high crystallinity and strong hydrophilicity of nanocellulose may cause the nanocellulose crystals to be brittle and have poor adhesion when used as a coating. Therefore, it is necessary to modify the nanocellulose crystals to improve their flexibility and adhesion on the PLA surface. The present invention improves the flexibility and adhesion of the nanocellulose crystal coating through a flexible polymer cross-linking strategy, thereby ensuring that the nanocellulose coating can give full play to its barrier performance advantages, thereby improving the overall performance of the PLA film. Summary of the invention

[0005] The purpose of the present invention is to provide a high-barrier flexible nanocellulose coating, a coating and a preparation method thereof. Through a simple coating method, a high-barrier flexible nanocellulose coating is prepared, which not only enhances the oxygen barrier effect of the polylactic acid film, but also changes the flexibility and adhesion of the nanocellulose coating.

[0006] To achieve the above object, the first aspect of the present invention provides a method for preparing a high barrier flexible nanocellulose coating, comprising the following steps:

[0007] (1) using an oxidant to oxidize the nanocellulose dispersion to obtain a dialdehyde nanocellulose (DAC) dispersion;

[0008] (2) adding cysteine ​​to the dialdehyde nanocellulose dispersion and reacting in a water bath to obtain a thiol-modified nanocellulose (CNC-cys) solution;

[0009] (3) Adding polyethylene glycol diacrylate (PEGDA) crosslinker and photoinitiator to the thiol-modified nanocellulose solution and stirring evenly to obtain a nanocellulose-based CNC-cys-PEG coating.

[0010] Furthermore, in step (1), the oxidant is sodium periodate, and the molar ratio of the monomer in the nanocellulose to the sodium periodate is 1:(1-4).

[0011] Furthermore, the mass concentration of the nanocellulose dispersion is 0.1wt%-22wt%, preferably 0.5-1wt%; the oxidation reaction is carried out in a dark environment, at a reaction temperature of 30-40°C, for 4-8h, preferably 6h, and at a stirring speed of 400r / min.

[0012] Furthermore, step (1) further comprises: after the oxidation reaction is completed, adding ethylene glycol to decompose the remaining sodium periodate for 10 min-30 min, and then dialyzing in deionized water to obtain a dialdehyde nanocellulose dispersion; the mass ratio of the sodium periodate (referring to that added in step (1)) to ethylene glycol is 1:(1.5-2).

[0013] Specifically, a 1wt% CNC dispersion was fully mixed with an equal mass of deionized water in a flask, stirred evenly after adding sodium periodate, and heated in a water bath. During this process, sodium periodate oxidized the two active hydroxyl groups on the surface of nanocellulose into aldehyde groups. After the reaction was completed, ethylene glycol was added to decompose the remaining sodium periodate to obtain a light yellow dispersion. Subsequently, the liquid was dialyzed to remove unreacted solvents and impurities in the solution.

[0014] Furthermore, in step (2), the molar ratio of the dialdehyde nanocellulose to cysteine ​​is 1:(1.8-2.2), preferably 1:2; the temperature of the water bath is 45-55°C, preferably 50°C, the reaction time is 4-8h, the stirring speed is 600r / min, and after the reaction is completed, the thiol-modified nanocellulose solution is obtained by dialyzing in deionized water.

[0015] Furthermore, in step (3), the molar ratio of the polyethylene glycol diacrylate (Mn=1000) to the monomer in the nanocellulose is 1:(10-20).

[0016] Furthermore, in step (3), the photoinitiator is Irgacure 2959 (2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone), and the mass of the photoinitiator is 8-12% of the mass of the nanocellulose in the nanocellulose dispersion of step (1), preferably 10%.

[0017] Dialdehyde nanocellulose reacts with cysteine ​​to synthesize thiol nanocellulose (CNC-cys). Then, CNC-cys is mixed with a crosslinker and a photoinitiator, and crosslinked by ultraviolet light to obtain CNC-cys-PEG gel. During the polymerization process, the thiol groups on CNC-cys crosslink with the carbon-carbon double bonds at the ends of the PEGDA (Mn=1000) molecules to form a high-density network structure. By adjusting the amount of PEGDA (Mn=1000), the degree of grafting can be controlled to prepare a nanocellulose gel coating.

[0018] A second aspect of the present invention provides a high-barrier flexible nanocellulose coating, which is obtained by curing the coating obtained by the preparation method.

[0019] The third aspect of the present invention provides a high-barrier polylactic acid film, comprising a polylactic acid film substrate and the above-mentioned high-barrier flexible nanocellulose coating coated on the polylactic acid film substrate.

[0020] Furthermore, the coating obtained by the preparation method described above is coated on a polylactic acid film substrate, then cured by ultraviolet light to obtain a hydrogel coating, and then naturally dried to obtain the high-barrier flexible nano-cellulose coating; the thickness of the high-barrier flexible nano-cellulose coating is 5-10 μm, and the specific thickness can be adjusted by the scraper spacing; the water content in the hydrogel coating is 30-95wt%.

[0021] The specifications of the base PLA film are: 20cm×20cm, thickness: 45-50μm.

[0022] In general, the above technical solution conceived by the present invention has the following advantages and beneficial effects compared with the prior art:

[0023] 1. The present invention uses nanocellulose crystals as raw materials to react in aqueous solution, first performs sodium periodate oxidation, then further introduces thiol groups by Schiff base reaction, adds PEGDA crosslinking agent in proportion, and uses a coating machine to apply the coating to the surface of the polylactic acid film, thereby avoiding the problem of uneven coating and uneven thickness, and finally obtains the CNC-cys-PEG functional coating by ultraviolet irradiation. Compared with the prior art, the present invention has the advantages of being green and environmentally friendly, being carried out in aqueous solution, not requiring the addition of any organic solvent, having a simple preparation process, and having low cost. In addition, the coating has a dense crosslinked network gel structure, a smooth surface, a transparent coating, and good flexibility and oxygen barrier effect.

[0024] 2. The present invention utilizes the thiol group on CNC-cys to cross-link with the double bond at the end of the PEGDA molecule to form a high-density network structure. By adjusting the amount of PEGDA, the degree of grafting can be controlled, thereby preparing a nanocellulose gel coating with good barrier properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Infrared spectra of nanocellulose crystals (CNC), dialdehyde nanocellulose (DAC), thiol-modified nanocellulose (CNC-cys), CNC-cys-PEG coating and PEGDA.

[0026] Figure 2 C1s XPS peak spectra of nanocellulose crystals (CNC), dialdehyde nanocellulose (DAC), thiol-modified nanocellulose (CNC-cys), and CNC-cys-PEG coatings.

[0027] Figure 3 XRD patterns of nanocellulose crystals (CNC), dialdehyde nanocellulose (DAC), thiol-modified nanocellulose (CNC-cys), CNC-cys-PEG coating, and PEGDA.

[0028] Figure 4 This is the change curve of the molar ratio of nanocellulose to crosslinker PEGDA-solution viscosity.

[0029] Figure 5 Coating and UV-crosslinking process for CNC-cys-PEG coating.

[0030] Figure 6 Appearance and flexibility of unmodified nanocellulose and CNC-cys-PEG coated modified PLA films.

[0031] Figure 7 SEM images of nanocellulose (a, b, c) and dialdehyde nanocellulose (d, e, f), CNC-cys (g, h, i) and CNC-cys-PEG coatings (j, k, l).

[0032] Figure 8 is the oxygen permeability of pure PLA film and PLA / CNC-cys-PEG coating composite membrane (cm 3 / (m 2 ·24h·0.1MPa))Test result chart.

[0033] Fig. 9 This is a diagram showing the preparation principle and oxygen barrier performance of the high-barrier flexible nanocellulose coating of the present invention. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0035] In a specific embodiment, the nanocellulose ((C6H 10 O5) n The amount of monomer substance n = 0.00617 mol, diameter 10nm, length 100-200nm) content is 1wt% (m 纯CNC =1g); the amount of PEGDA added is 5% n CNC (i.e. the molar ratio of monomer and PEGDA in nanocellulose n CNC :n PEGDA =20:1).

[0036] Example 1

[0037] 1 wt% nanocellulose dispersion (m 纯CNC=1g) and an equal mass of deionized water were mixed in a flask. Under light-proof conditions, 0.00617mol of sodium periodate was added, the reaction was stirred at 400r / min, and the reaction was carried out in a 40°C water bath for 6h to oxidize the two active secondary hydroxyl groups on the surface of the nanocellulose to aldehyde groups. After the reaction was completed, ethylene glycol was added to decompose the remaining sodium periodate (the mass ratio of sodium periodate to ethylene glycol was 1:1.5), and the time used was 15min. The light yellow dispersed liquid was then dialyzed in deionized water for 72 hours (molecular weight cutoff: 7000kDa).

[0038] According to Example 1, 1 wt% of nanocellulose dispersion (m 纯CNC =1 g) was mixed with an equal mass of deionized water to reduce the nanocellulose concentration to 0.5 wt%.

[0039] Example 2

[0040] The dialyzed dialdehyde nanocellulose (DAC) dispersion was mixed evenly with 0.0123 mol of cysteine, placed in a 50°C water bath, and stirred with a magnetic stirrer at 600 r / min for 6 hours. At this time, two thiol groups were introduced into the dialdehyde nanocellulose to obtain thiol nanocellulose, forming a light yellow transparent solution. It was then dialyzed in deionized water for 72 hours (molecular weight cutoff: 7000 kDa).

[0041] Example 3

[0042] According to n CNC :n PEGDA =20:1, PEGDA (Mn=1000) crosslinking agent is added to the mercapto nanocellulose solution, and 0.1g of photoinitiator Irgacure 2959 is added, and the coating is prepared by stirring evenly. The coating is applied to a polylactic acid film substrate (specification: 20cm×20cm, thickness: 45-50μm), and the thickness of the coating (2-10μm) is controlled by controlling the gap between the scraper and the PLA film, and then irradiated with a 10W 365nm ultraviolet lamp for 15-20min to obtain a hydrogel crosslinked coating, the water content of the hydrogel coating is 95wt%, and then naturally dried for 2 hours to obtain the high barrier flexible nanocellulose coating.

[0043] In the embodiment, the relevant test contents are as follows:

[0044] like Figure 1 , the functional groups of nanocellulose (CNC), dialdehyde nanocellulose (DAC), thiol nanocellulose (CNC-cys) and CNC-cys-PEG coating (i.e., high-barrier flexible nanocellulose coating after cross-linking) were characterized using Fourier transform infrared spectrometer IS10. Figure 1The results show that there is an obvious absorption peak at 3343cm-1, which is attributed to the -OH group; the peak at 2904cm-1 is the characteristic of CH vibration; and the peak at 1032cm-1 represents the stretching vibration of CO. In the spectrum of DAC, the peak at 1724cm-1 corresponds to the absorption of the aldehyde group (C=O), indicating that the hydroxyl group has been successfully oxidized to the aldehyde group. After graft copolymerization, the ester group C=O peak and the methylene CH peak in the spectrum of CNC-cys-PEG are significantly enhanced. In addition, the peak at 1637cm-1 is the characteristic peak of C=C of the PEGDA molecule, and the peak at 1291cm-1 is attributed to the presence of the ether bond COC.

[0045] like Figure 2 The XPS C1s peak analysis results show that peak A (283.5 eV), peak B (285 eV) and peak C (286.7 eV) correspond to the signals of C-OH, CC / CH and COC / C=O, respectively, and appear in CNC, DAC, CNC-cys and CNC-cys-PEG. During the oxidation process, the conversion of the C2-C3 bond in CNC leads to the conversion of the hydroxyl group to the aldehyde group. This change is manifested in the C1s data as a decrease in peak B and an increase in peak C. Peak D (287.8 eV) is attributed to the O=CO signal of the carboxylate group. In addition, peak E (283.2 eV) further confirms the existence of the CSC / C=N group.

[0046] like Figure 3 , from CNC to CNC-cys-PEG, the nanocellulose crystal structure did not change at all and still maintained the cellulose type I structure.

[0047] like Figure 4 , the study showed that the effect of the molar ratio of nanocellulose to PEGDA on the viscosity of the solution changed significantly, which in turn affected the coating processing performance. The results showed that as the PEGDA content increased, the solution viscosity gradually increased; conversely, as the PEGDA content decreased, the solution viscosity decreased. At the same time, the nanocellulose / PEGDA molar ratio affects the flexibility and barrier properties of the CNC coating. However, when the PEGDA content is low, the flexibility of the CNC-cys-PEG coating is poor. When the PEGDA content is high, the voids inside the CNC-cys-PEG coating increase, and the barrier properties of the coating also decrease. The purpose and advantage of the present invention is to use a smaller amount of flexible polymer to improve the brittleness and adhesion of the CNC coating while ensuring the barrier properties of the coating.

[0048] like Figure 5 , describes the PLA membrane coating process of CNC-cys-PEG coating (see Figure 5 a and b), and after UV irradiation (see Figure 5The experiment showed that the CNC-cys-PEG coating had good adhesion to the PLA film, and the surface was uniform and transparent after coating (see Figure 5 (d)

[0049] like Figure 6 The surface of pure nanocellulose coating is relatively fragile, and the adhesion between the coating and the PLA substrate film is poor. After adding PEGDA cross-linking, the nanocellulose coating becomes more flexible and has enhanced crack resistance. At the same time, the adhesion between the nanocellulose coating and the PLA film is significantly improved.

[0050] like Figure 7 Scanning electron microscope (SEM) observation of the example products showed that the CNC, DAC and CNC-cys samples were fragmented (see Figure 7 The surface density of CNC-cys-PEG after grafting was significantly improved (see Figure 7 c, f, i, l), indicating that the barrier properties of the nanocellulose coating are enhanced. The prepared CNC-cys-PEG coating has good adhesion to the PLA film, and the SEM cross-sectional image shows that the coating thickness is 2.0 to 10.0 μm (see Figure 7 (k).

[0051] like Figure 8 By comparing the test results, we can see that the oxygen barrier performance of PLA film (thickness: 45-50μm) is relatively general. The oxygen permeability of PLA composite film (coating thickness: 2-10μm) coated with CNC coating is significantly reduced, indicating that the coating of nanocellulose coating effectively improves the barrier performance of PLA film.

[0052] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high barrier flexible nanocellulose coating and coating, characterized in that: The following steps are involved: (1) using an oxidant to oxidize the nanocellulose dispersion to obtain a dialdehyde nanocellulose dispersion; (2) adding cysteine ​​to the dialdehyde nanocellulose dispersion and reacting them in a water bath to obtain a thiol-modified nanocellulose solution; (3) Adding polyethylene glycol diacrylate crosslinking agent and photoinitiator to the thiol-modified nanocellulose solution and stirring evenly to obtain a nanocellulose-based coating.

2. The method for preparing the high barrier flexible nanocellulose coating according to claim 1, characterized in that: In step (1), the oxidant is sodium periodate, and the molar ratio of the monomer in the nanocellulose to the sodium periodate is 1:(1-4).

3. The method for preparing the high barrier flexible nanocellulose coating according to claim 1, characterized in that: The concentration of the nanocellulose dispersion is 0.1wt%-22wt%, preferably 0.5-1wt%; the oxidation reaction is carried out in a light-proof condition, at a reaction temperature of 30-40°C and for 4-8h.

4. The method for preparing the high barrier flexible nanocellulose coating according to claim 2, characterized in that: Step (1) further comprises: after the oxidation reaction is completed, adding ethylene glycol to decompose the remaining sodium periodate for 10 min to 30 min, and then dialyzing in deionized water to obtain a dialdehyde nanocellulose dispersion; the mass ratio of the added sodium periodate to the ethylene glycol is 1:(1.5-2).

5. The method for preparing the high barrier flexible nanocellulose coating according to claim 1, characterized in that: In step (2), the molar ratio of the dialdehyde nanocellulose to cysteine ​​is 1:(1.8-2.2), the temperature of the water bath is 45-55°C, the reaction time is 4-8h, and after the reaction is completed, the thiol-modified nanocellulose solution is obtained by dialyzing in deionized water.

6. The method for preparing the high barrier flexible nanocellulose coating according to claim 1, characterized in that: In step (3), the molar ratio of the polyethylene glycol diacrylate to the monomer in the nanocellulose is 1:(10-20).

7. The method for preparing the high barrier flexible nanocellulose coating according to claim 1, characterized in that: In step (3), the photoinitiator is Irgacure 2959, and the mass of the photoinitiator is 8-12% of the mass of the nanocellulose.

8. A high barrier flexible nanocellulose coating, characterized in that: The coating is obtained by curing the coating obtained by the preparation method according to any one of claims 1 to 7 through ultraviolet light.

9. A high barrier polylactic acid film, characterized in that: The invention comprises a polylactic acid film substrate and the high-barrier flexible nanocellulose coating according to claim 8 coated on the polylactic acid film substrate.

10. The high barrier polylactic acid film according to claim 9, characterized in that: The coating obtained by the preparation method according to any one of claims 1 to 7 is applied to a polylactic acid film substrate, and then cured by ultraviolet light to obtain a hydrogel coating, and then naturally dried to obtain the high-barrier flexible nanocellulose coating; The thickness of the high barrier flexible nanocellulose coating is 5-10 μm; the thickness of the polylactic acid film substrate is 45-50 μm; and the water content of the hydrogel coating is 30-95 wt%.

Citation Information

Patent Citations

  • CNC / PEG composite coating and preparation method thereof

    CN106590179A

  • High-toughness biaxially oriented polylactic acid film, preparation method and application thereof

    CN112608502A

  • Inkjet primer compositions containing nanocellulose

    EP4397728A1

  • Nanocellulose dispersion composition and coating composition

    JP2019123827A

  • KR20210094819A